Ai-supported development of a humanitarian character education model for rural Malaysian preschools: Historical perspectives and lessons from Japan - Lee, Bih Ni; Connie Shin @ Connie Cassy Ompok (Zenodo, 2025)
This study explores the development of an AI-supported humanitarian character education model tailored for rural Malaysian preschools, informed by historical perspectives and educational philosophies from Japan. Using a mixed-methods approach, researchers collected primary quantitative and qualitative data through AI-assisted online tools, enabling efficient engagement with educators and stakeholders across diverse rural settings. Additionally, secondary data—including educational policies, historical frameworks, and scholarly literature from both Malaysia and Japan—were analyzed through a Mixed-Methods Secondary Data Analysis (MMSDA) framework. Drawing from Japanese models such as Makiguchi’s value-creating pedagogy and Obara’s whole-person education, the study identifies culturally adaptable principles that can inform the integration of moral and character education in rural preschool environments. The findings propose a conceptual framework that leverages AI technology while honoring local values and pedagogical integrity, offering a scalable solution for character formation in early childhood education.